Attaining a British consensus on managing idiopathic congenital talipes equinovarus up to walking age. (1st June 2022) - Gelfer, Yael; Davis, Naomi; Blanco, Jose; Buckingham, Rachel; Trees, Amanda; Mavrotas, Jason; Tennant, Sally; Theologis, Tim
Abstract : Aims: The aim of this study was to gain an agreement on the management of idiopathic congenital talipes equinovarus (CTEV) up to walking age in order to provide a benchmark for practitioners and guide consistent, high-quality care for children with CTEV. Methods: The consensus process followed an established Delphi approach with a predetermined degree of agreement. The process included the following steps: establishing a steering group; steering group meetings, generating statements, and checking them against the literature; a two-round Delphi survey; and final consensus meeting. The steering group members and Delphi survey participants were all British Society of Children's Orthopaedic Surgery (BSCOS) members. Descriptive statistics were used for analysis of the Delphi survey results. The Appraisal of Guidelines for Research & Evaluation checklist was followed for reporting of the results. Results: The BSCOS-selected steering group, the steering group meetings, the Delphi survey, and the final consensus meeting all followed the pre-agreed protocol. A total of 153/243 members voted in round 1 Delphi (63%) and 132 voted in round 2 (86%). Out of 61 statements presented to round 1 Delphi, 43 reached 'consensus in', no statements reached 'consensus out', and 18 reached 'no consensus'. Four statements were deleted and one new statement added following suggestions from round 1. Out of 15 statements presented to round 2, 12 reached 'consensus in', no statements reached 'consensus out', and three reached 'no consensus' and were discussed and included following the final consensus meeting. Two statements were combined for simplicity. The final consensus document includes 57 statements allocated into six successive stages. Conclusion: We have produced a consensus document for the treatment of idiopathic CTEV up to walking age. This will provide a benchmark for standard of care in the UK and will help to reduce geographical variability in treatment and outcomes. Appropriate dissemination and implementation will be key to its success. Cite this article: Bone Joint J 2022;104-B(6):758–764.